Modelo de algoritmo para la estandarización de la clasificación de variantes genéticas obtenidas por NGS según recomendaciones ACMG-AMP y Sherloc en una cohorte de pacientes pediátricos con patologías nefrológicas - Riera, Luisina Ayelen (2023)
Whole exome analysis by NGS has become a frequent request as a guide for decision making on prevention, diagnosis and/or treatment of pathologies with suspected genetic origin, in addition to providing family counseling. Given the great complexity of variant analysis and its classification, revisions and publications with the intention of standardizing it are continuous. We chose a cohort of 10 pediatric patients with different renal pathologies with high suspicion of genetic etiology. Their analysis was performed based on the international variant classification guideline performed by the ACMG-AMP (Richards et al., 2015) and on the Sherloc guideline (Nykamp et al., 2017), in order to compare both their approaches and results as well. In 70% of the cases it was possible to identify variants associated with the phenotype of the patients, which were classified as pathogenic, likely pathogenic and variants associated with risk factors for the development of renal pathology. Based on the results obtained, it was possible to describe an algorithm for variant analysis on the basis of based on the ACMG-AMP and Sherloc rules that would unify criteria and be applicable to other types of variants that are not covered by these rules. We also demonstrated the need for interdisciplinary work, the importance of whole exome kit sequencing, and, last but not least, we proved that although automated analysis platforms, although they reduce and smooth the path to identification of clinically significant variants, the intervention of experts in the field is still essential to provide reports that integrate the particular evidence of each case.